Correlation between Allergic Rhinitis and Rhinosinusitis in ENT Outpatient Clinic Patients - Felicia Alvita Tjahjono; Irwan Kristyono; Ari Baskoro (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: Rhinosinusitis and allergic rhinitis are common health problems. Allergic rhinitis patients tend to have edema on their nasal mucosa, disrupted cilia, and excessive secrete production that clogged paranasal sinuses’ ostiums and lead to inflammation and infection of the paranasal sinuses. There is still a contradiction of allergic rhinitis as predisposing factor of rhinosinusitis. Those correlation is not yet clear, thus we aim to analyze the correlation between allergic rhinitis and rhinosinusitis.Methods: This study was a cross-sectional design. The samples were obtained by consecutive sampling. Adult patients above 19 years old with nasal discharge were examined by the doctors on duty and interviewed. Medical data obtained was recorded and analyzed using chi square test.Results: From 98 patients, 17 patients (17.35%) had both rhinosinusitis and allergic rhinitis, 48 patients (48.98%) only had rhinosinusitis, and 13 patients (13.26%) only had allergic rhinitis. Patients who had neither rhinosinusitis nor allergic rhinitis reported to be 20 patients (20.41%). Chi square test showed that allergic rhinitis had no significant correlation with rhinosinusitis (p=0.266).Conclusion: There is no significant correlation between allergic rhinitis and rhinosinusitis. Rhinosinusitis is a multifactorial disease.